Continuity and change in the institution of town and country planning: Modelling the role of ideology. (November 2018) - Shepherd, Edward
The institution of town and country planning rests upon ideas and concepts which will always be contested. Such concepts include 'liberty', 'community', 'society' and 'the state'. It is a function of political ideology to seek to fix the meanings of contested concepts and thus exert control over political reality. By analysing the particular conceptual structure of the ideologies which seek to influence planning from positions of political power, the analyst can show how these ideologies are related to shifts in the conceptual and institutional structure of planning. The article illustrates this analytical method in the context of the transition from the ideology of New Labour to the ideology of the Conservative-led Coalition government in England after 2010.